Relationship between Social Dysfuction Factors and Femicide Cases among Young Women in Juja Sub-County, Kenya (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Femicide has increased in the last decade in the global index. In Kenya, femicide occurs under diverse age brackets but recently the trend is high among young women (16-35 years). In particular, the brutal murders of young women: emerging and with increasing trends and incidents in various places call for immediate solutions. The purpose of this study was to examine relationship between social dysfuctions and femicide cases among young women in Juja sub-county. The Feminist theory and Routine activity theory guided the study. The study was done at Juja sub-County in Kiambu County, Kenya. The study adopted a mixed–method research approach, utilizing the embedded design. The target population was 300,948 respondents. The accessible population was 200,510 respondents, out of which a sample of 278 was drawn through the Slovin's formula. The total sample was 288 respondents consisting of the 10 key informants included in the study. The researcher drew the sample using Stratified simple random sampling. Questionnaires and interview schedules were the main instruments of data collection where 245 questionaires were fully filled and returned and all the 10 interviews were conducted succesfully. Reliability was measured through Cronbach Alpha a statistic coefficient (a value between 0 and 1) used to rate the reliability of an instrument and was 0.813. Poisson regression analysis was conducted on the quantitative data with the help of Statistical Package for Social Sciences (SPSS) version 26.0 software. Qualitative data was analysed through thematic content analysis utilizing MAXQDA tool. The study established no statistically significant relationship between social factors and femicide with a p-value of .367, well above the .05 threshold, the model indicated that social variables do not have a direct, independent effect on the number of femicide cases. The study concluded that social dysfunctions alone are not the cause of femicide but is as a result of a more complex, multi-faceted dynamic at play than a simple cause-and-effect and recommended that to reduce these risks, there is a need for strengthened social support systems. The study aimed to benefit the policymakers on formulating relevant social policies, inform the society on better societal practices, contribute to the academia theories and literature on femicide, as well as inform young women in adopting femicide prevention strategies.